2018
DOI: 10.1177/0067205x1804600201
|View full text |Cite
|
Sign up to set email alerts
|

The use of Foreign Law by the High Court of Australia

Abstract: Justices of the High Court of Australia have a broad discretion to follow foreign judicial decisions based on whether they consider a decision to be persuasive. But it is difficult to assess what it is about a foreign decision that makes it likely to be followed by the High Court. This has created uncertainty that is problematic for both litigants and the court. To help address the uncertainty associated with the High Court's use of foreign decisions, this article identifies common factors that explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A survey of US federal court case law citation practice between 1945 and 2005 revealed that citation of foreign decisions is a relatively rare phenomenon in the United States that is generally confined to cases where international issues are squarely presented by the facts [28]. In Australia, an analysis of decisions of the High Court of Australia between 2015 and 2016 found that court tended to cite foreign judicial decisions emanating from jurisdictions that reflect values common to the Australian legal system, particularly where the cited case considers statutory language that is similar to that which is in dispute [29]. Most recently, an analysis of United Kingdom Supreme Court decisions found that citations to foreign jurisprudence occurred in just under 30% of that court's decisions [30].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of US federal court case law citation practice between 1945 and 2005 revealed that citation of foreign decisions is a relatively rare phenomenon in the United States that is generally confined to cases where international issues are squarely presented by the facts [28]. In Australia, an analysis of decisions of the High Court of Australia between 2015 and 2016 found that court tended to cite foreign judicial decisions emanating from jurisdictions that reflect values common to the Australian legal system, particularly where the cited case considers statutory language that is similar to that which is in dispute [29]. Most recently, an analysis of United Kingdom Supreme Court decisions found that citations to foreign jurisprudence occurred in just under 30% of that court's decisions [30].…”
Section: Related Workmentioning
confidence: 99%
“…Assumption 3: Geographic proximity: Homophily, the principle that similarity breeds connection, has been found to influence a range of network settings, including paper citation networks [52] and social networks [53]. A recent study examining an Australian case law citation network observed that judges in that country generally favoured the jurisprudence of countries that reflect their social values and legal traditions [29]. There are any number of points of similarity between national legal systems, including socioeconomic factors, language, style of constitution and government.…”
Section: Considerations Relevant To the Citation Of Foreign Case Lawmentioning
confidence: 99%
See 1 more Smart Citation